Kikuchi–Fujimoto Disease in an Old Italian Woman: Case Report and Review of the Literature. (14th December 2017) - D'Introno, A.; Perrone, A.; Schilardi, A.; Gentile, A.; Sabbà, C.; Napoli, N.
Abstract : Kikuchi–Fujimoto disease (KFD) is a rare, benign, generally self-limiting disease that has higher prevalence in Asian people with a few cases reported in European countries. It generally affects young subjects under 40 years of age and is characterized by regional lymphadenopathy. Here, we present a case of a 66-year-old Italian woman who was extensively examined for right unilateral laterocervical lymph nodes associated with fever, night sweats, fatigue, and weight loss. She was diagnosed as having the KFD only after an excision biopsy of the largest laterocervical lymph node and was then managed symptomatically with NSAIDs. We also made a review of the literature for better awareness of the disease among physicians especially in those countries, like Italy, where the disease is not prevalent and may be frequently misdiagnosed. In fact, to our best knowledge, only seven Italian cases of KFD have been published in the last 15 years with patients being younger than 40 years. We finally highlight that it is noteworthy to consider KFD as differential diagnosis of lymphadenopathy even in old patients, and, since a misdiagnosis of lymphoma is actually feasible, an early biopsy has to be taken into account for confirming diagnosis and helping in the timely and appropriate management.